Transfer of learning in the field of recreation - Peters Maki, Lynne (My University, 1992)
The intent of the study Transfer of Learning in the Field of Recreation was to determine if the students in the Recreation Leadership program at Confederation College could transfer the skills and principles learned in the classroom to practical applications in the field. Through qualitative research methods the researcher set out to determine: (1) if the curriculum taught in the classroom was applicable to the field; (2) if the students demonstrated, with confidence, the skills, strategies and concepts taught in the classroom out in the field; and (3) what gaps existed between the practices occurring in the field and the curriculum taught in the course. In Phase I course outlines were analyzed and a list of the skills, strategies and concepts recommended as intended course outcomes was developed. This list was compared with the DACUM, a chart developed by the Ministry of Colleges and Universities, to identify intended program outcomes for graduating students. In Phase II the researcher collected data on seven students out on internship to determine the skills, concepts and strategies demonstrated in the field. Methods of data collection included observations, interviews and document analysis of journals and monthly reports. During Phase III the researcher used comparative analysis to determine if the actual outcomes demonstrated by the students in the field were the same as the skills, strategies and concepts identified in the course outlines and in the DACUM. The intent of the researcher was to determine the link between the intended program outcomes and the actual program outcomes. The findings focused on three key areas: internship and the value of field placements to increase student confidence levels; curriculum revision based on the findings from Phase I and Phase III of the study; and, using the research design and methodologies outlined in this study as a viable model for curriculum evaluation and development. The study provided the researcher with an opportunity to look at the existing curriculum practices and compare them to what is happening in the field of recreation. The findings and recommendations could have a positive impact on both the Recreation Leadership program at Confederation College and the field of recreation.
Keywords: Transfer of training; Recreation leadership